B and T cell responses to the 3rd and 4th dose of the BNT162b2 vaccine in dialysis patients - Younes Bathish; Neta Tuvia; Elizabeth Eshel; Tali Tal Lange; Christiane Sigrid Eberhardt; Michael Edelstein; Kamal Abu-Jabal (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTPatients on dialysis (PoD) are at high risk of severe morbidity and mortality from COVID-19. Characterizing long-term vaccine immune responses in these patients will help optimize vaccine schedule for PoD. This study aimed to determine whether long-term humoral and B and T cell-responses post 3rd and 4th dose of the BNT162b2 vaccine differed between PoD and controls. Non-infected PoD and controls vaccinated with BNT162b2 were recruited in Ziv Medical Center, Israel, between 2021 and 2022. Specimens were collected 1–2 months pre 3rd dose; 1–3 months post 3rd dose; 4–5 months post 3rd dose and 3–5 months post the 4th dose. Anti-SARS-CoV-2 spike (spike) specific antibodies, spike specific memory B cells, and spike specific CD154+ T cells as well as cytokines producing CD4+/CD8+ T cells were measured using standardized assays and compared between PoD and controls at each time point using Mann Whitney and Fisher’s exact tests. We recruited 22 PoD and 20 controls. Antibody levels in PoD were lower compared to controls pre 3rd dose but not post 3rd and 4th doses. Frequencies of spike specific memory B cell populations were similar between PoD and controls overall. Frequencies of spike specific T cells, including those producing IFNγ and TNFα, were not lower in PoD. B and T cell mediated immune response in PoD following a 3rd and a 4th dose of the BNT162b2 vaccine was not inferior to controls up to 5 months post vaccination. Our results suggest that standard BNT162b2 vaccination is suitable for this group.